A comparative study on work surface hardness EDMed by Ta-C powder compacted and copper electrodes - Khan, Ahsan Ali; Nazi Nadin, Mohd Faiz; Mohd Hambiyah, Mohammad Azhadi (International Islamic University Malaysia, 2011)
Abstract. Tantalum-carbide and solid copper electrodes were used to EDM mild steel. Current, spark on-time and off-time were taken as the machining variables. It was found that work surface hardness increases while machining with high current and on-time. However, increase in spark off-time results decrease in work surface hardness. It was also found that the surface machined with pure copper electrodes is harder than that machined by tantalum-carbide powder metallurgy compacted electrodes.